Effect of body tilt angle on fatigue and EMG activities in lower limbs during cycling - Egana, Mikel (My University, 2010)
This study compared the rate of fatigue and lower limb EMG activities during high-intensity constantload cycling in upright and supine postures. Eleven active males performed seven cycling exercise tests: one upright graded test, four fatigue tests (two upright, two supine) and two EMG tests (one upright, one supine). During the fatigue tests participants initially performed a 10 s all-out effort followed by a constant-load test with 10 s all-out bouts interspersed every minute. The load for the initial two fatigue tests was 80% of the peak power (PP) achieved during the graded test and these continued until failure. The remaining two fatigue tests were performed at 20% PP and were limited to the times achieved during the 80% PP tests. During the EMG tests subjects performed a 10 s all-out effort followed by a constant-load test to failure at 80% PP. Normalised EMG activities (% maximum, NEMG) were assessed in five lower limb muscles. Maximum power and maximum EMG activity prior to each fatigue and EMG test were unaffected by posture. The rate of fatigue at 80% PP was significantly higher during supine compared with upright posture (-68 ? 14 vs. -26 ? 6 W min-1, respectively, P\0.05) and the divergence of the fatigue responses occurred by the second minute of exercise. NEMG responses were significantly higher in the supine posture by 1?4 min of exercise. Results show that fatigue is significantly greater during supine compared with upright high-intensity cycling and this effect is accompanied by a reduced activation
PUBLISHED
Keywords: posture; performance; exercise; muscle activity; Next Generation Medical Devices